KARAKTER ORANG MADURA DAN FALSAFAH POLITIK LOKAL - Ainurrahman Hidayat (Karsa: Journal of Social and Islamic Culture)
Abstrac This article attempts to explore the basic character of Madurese people that put the moral-ethic basics on every attitude, utterances, and behavior of Madurese local politic phenomena. The study results four basic characteristics of Madurese---ejhin, koko, gherra and saduhunah. Those become local wisdom of Madurese people. The four basic characters should have introduced and provided each Madurese local politic phenomena to reach a better politic life. Ejhin character carries a tolerant nature, friendship and dependent.  Koko character introduces loyality, consistency, trust and responsibility. Gherra character reflects carefulness, transparency, and fairness. Saduhunah describes honesty and innocent. Kata-kata kunci ejhin, gherra, koko, saduhuna